Recovery for performance in sport (INSEP, 2013)
The book contains 17 chapters written by more than 30 international experts and provides the most comprehensive and up-to-date scientific and practical information about recovery in sport. In addition, readers can find case studies describing recovery strategies that have been used successfully by world-class sport scientists, coaches and athletes. These case studies complement nicely the scientific information contained in the book and bring such information to the context of real life training and competition situations. (Heruasgeberinformation)